The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Sweden. (4th May 2017) - Marton, Jan
Abstract: In this paper, the influence of IFRS on Swedish national accounting rules is analyzed. The lawmaker's and standard setters' response to EU Accounting Directive 2013/34/EU is studied, as well as the use of IFRS in enforcement. The conclusion is that IFRS have a strong position and legitimacy in Swedish financial reporting.